2020
DOI: 10.1186/s41182-020-00273-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vertical HIV infection and its risk factors among HIV exposed infants in East Africa: a systematic review and meta-analysis

Abstract: Background Human immunodeficiency virus (HIV) is one of the most important global health problems. More than one and half million of children are living with HIV in the world, and majority of them are found in sub-Saharan Africa. There are primary fragmented study findings, and no review was conducted with regard to vertical HIV infection in East Africa. Therefore, this review aimed to assess the prevalence of vertical HIV infection and its risk factors among HIV-exposed infants in East Africa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 48 publications
7
23
2
Order By: Relevance
“…In contrast to our nding other studies from different parts of the world as well as Ethiopia obtained high prevalence [11,[22][23][24][25][26][27][28][29]. Furthermore, a study reported from Addis Ababa indicated higher prevalence (4.2%) of HIV infection in HEI [13] than the current study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our nding other studies from different parts of the world as well as Ethiopia obtained high prevalence [11,[22][23][24][25][26][27][28][29]. Furthermore, a study reported from Addis Ababa indicated higher prevalence (4.2%) of HIV infection in HEI [13] than the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…This result was similar with previous studies reported from different settings [10,[13][14]19], 26, 29]. Moreover, in-line with our result, ndings reported by review studies indicated that infants on nevirapine prophylaxes were at lesser risk of HIV infection than those who missed the service [16,25]. These indicate that nevirapine prophylaxis could prevent MTCT of HIV during breastfeeding.…”
Section: Discussionsupporting
confidence: 93%
“…The rate of transmission of HIV from an HIV-positive mother to her baby ranges from 15 percent to 45 percent in the absence of intervention and can be reduced to below 5 percent with an effective intervention [ 9 ]. Child born from HIV mother is at risk of contracting the disease [ 10 , 11 ]. The MTCT of HIV, which is also known as ‘vertical transmission’, accounts for the majority of infections in children aged 0–14 years [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The MTCT of HIV, which is also known as ‘vertical transmission’, accounts for the majority of infections in children aged 0–14 years [ 8 , 12 ]. A systematic review and meta-analysis done using 33 published article depicted that the pooled prevalence of MTCT of HIV in the East Africa is 7.68% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Important to note, it is relevant nowadays that HIV-positive pregnant woman bet understand the obstetrical risks associated with HIV infection, reinforcing that the sh duration of broken membranes could be associated with less vertical transmission [26] Furthermore, there was no other association between mode of delivery and H infection in our study, although no HIV transmission was registered in 196 patients fro Constanta RC and 119 patients from Craiova RC who underwent elective cesarean sectio We believe that elective cesarean section should be reserved to those patients with higher viral load or those who presented late in delivery without any cART treatment, with poor adherence at cART [27][28][29][30], considering that caesarean scars could lead to oth diseases such asendometriosis [31] in the future, which could causeinfertility, chro pelvic pain, dysmenorrhea, and dyspareunia [32].…”
Section: Discussionmentioning
confidence: 99%